1996
DOI: 10.1111/j.1600-0838.1996.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of sports injuries in schoolaged children

Abstract: In the 5‐year‐period 1988‐1992, 6096 children aged 6‐17 (54.5% boys and 45.5% girls) were treated at the Emergency Department at Esbjerg Central Hospital after having sustained a sports injury. The data were registred according to the European Home‐ and Leisure‐Accident Surveillance System (EHLASS) protocol. We found a total incidence rate in the municipality of Esbjerg of 73.3 per 1000 per year. Boys were most often injured in soccer, skateboard, handball, gymnastics and basketball, and girls in handball, hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 17 publications
3
13
1
3
Order By: Relevance
“…We found the general trend of increasing injury rate with advancing age starting with an incidence of 0.02% in age group 11e12 years and increasing to 1.57% in 17e18 years of age (Table 2). A similar finding was reported by Sorenson et al 6 showing sports and physical activity related injury rates of 20 per 1000 children at the age of 6, to 120 per 1000 children at the age of 14. This preponderance of injuries in adolescent years reflects a number of maturational and skeletal changes which occur during this time.…”
supporting
confidence: 76%
“…We found the general trend of increasing injury rate with advancing age starting with an incidence of 0.02% in age group 11e12 years and increasing to 1.57% in 17e18 years of age (Table 2). A similar finding was reported by Sorenson et al 6 showing sports and physical activity related injury rates of 20 per 1000 children at the age of 6, to 120 per 1000 children at the age of 14. This preponderance of injuries in adolescent years reflects a number of maturational and skeletal changes which occur during this time.…”
supporting
confidence: 76%
“…It remains unclear in the study of Sundblad et al 15 what was defined as leisure time PA. Even though the present study is the first to observe these gender differences in such a pronounced way, Sorensen et al 13 previously indicated that gender differences in injury risks “crossover” between the ages 12–14. This is presumably due to the growth spurt appearing earlier in girls.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, the majority of studies report on injuries sustained by a wide age range of children. However, as found by Sorensen et al 13 great variations in sports and PA injury rates exist between different ages, ranging from 20 per 1000 children at the age of 6, to 120 per 1000 children at the age of 14. The present study included only a relative small age range of 10–12-year-old children, rendering a comparison with other studies unhelpful.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…20 % bei Fußball) um Frakturen [8]. Der Großteil dieser Frakturen (76-88 %) betrifft die obere Extremität [14,15,21]. Meist werden dabei keine Handgelenkschoner getragen.…”
Section: Diskussionunclassified